Creating a culture of innovation : design an optimal environment to create and execute new ideas - Deschamps-Sonsino, Alexandra (Apress, 2020)
Deconstruct the history of patterns of innovation in business and connect them to existing and failed attempts in management consultancies, engineering, web technologies and academic institutions. This book shows you how to create an optimal environment at work for growth and innovation. Many large-scale organizations eventually invest in research and innovation as a dedicated part of their businesses. In doing so, they are faced with two choices: build their own practice of innovation or enact patterns of innovation created before them, ones they perceived as "tried and tested." In this book, you will see how patterns of innovation touch many aspects of a worker's life: from how their work is presented to others, job titles, working environment, and expectations around output. Every chapter will offer a history of these patterns and examples of how they have succeeded and failed within organizations. What You Will Learn Identify how innovation is named and highlighted in organizations Reveal ways to champion innovation to clients and the outside world, from trade shows and conferences inside the office Uncover ways companies acquire innovation, including incubators or mergers Discover the conditions for innovation to happen every day, including office layouts, time management, communication structures, and expectation management Who This Book Is For Tech start-up/scale-up founders, management consultants, managing directors, innovation managers and heads of R & D, academic researchers, interior designers, and architects